Peran Intelijen Ekonomi dalam Mempercepat Kesejahteraan Masyarakat Provinsi Gorontalo - Saksono, Herie; Humalanggi, Mahyudin; Lantapon, Nancy Noviana; Butolo, Ivana (Research and Development Agency Ministry of Home Affairs, 2023)
The Gorontalo Province region has the potential for significant resource wealth. However, the Gorontalo Provincial Government still faces problems and challenges when trying to improve the welfare of its people. One is the limited data/information that is accurate, up-to-date, and integrated. This data/information is important in planning and making appropriate decisions. Another problem is that the community's role in modern development based on economic intelligence in Gorontalo Province has not been optimal. This means that the public and even bureaucrats are still unfamiliar with